Variability in target delineation of cervical carcinoma: A Korean radiation oncology group study (KROG 15-06). - Ji Hyeon Joo; Young Seok Kim; Byung Chul Cho; Chi Young Jeong; Won Park; Hak Jae Kim; Won Sup Yoon; Mee Sun Yoon; Ji-Yoon Kim; Jin Hwa Choi; Youngmin Choi; Joo-Young Kim (PLoS ONE, 2017)
To determine inter-observer variability in target volume definition of cervical cancer in radical and adjuvant radiotherapy (RT) settings.Eight physicians contoured CTVs of 2 patients underwent definitive and postoperative RT. Each volume was analyzed using the individual/median volume ratio and generalized conformity index (CIgen). And center of mass (COM) of each contour was calculated. Expert agreement was quantified using an expectation maximization algorithm for Simultaneous Truth and Performance Level Estimation (STAPLE).For definitive RT, the individual/median volume ratio ranged from 0.51 to 1.41, and CIgen was 0.531. Mean 3-dimensional distances of average to each COM were 7.8 mm. For postoperative RT setting, corresponding values were 0.65-1.38, 0.563, and 5.3 mm. Kappa value of expert agreement was 0.65 and 0.67, respectively. STAPLE estimates of the sensitivity, specificity, and kappa measures of inter-physician agreement were 0.73, 0.98, and 0.65 for the definitive and 0.75, 0.98, and 0.67 for the adjuvant radiotherapy setting. The largest difference was observed in the superior-inferior direction, particularly in the upper vagina and the common iliac area.As there was still some variability in target delineation, more detailed guidelines for target volume delineation and continuing education would help to reduce this uncertainty.